2011
DOI: 10.1038/npp.2011.96
|View full text |Cite
|
Sign up to set email alerts
|

Phencyclidine-induced Loss of Asymmetric Spine Synapses in Rodent Prefrontal Cortex is Reversed by Acute and Chronic Treatment with Olanzapine

Abstract: Enduring cognitive deficits exist in schizophrenic patients, long-term abusers of phencyclidine (PCP), as well as in animal PCP models of schizophrenia. It has been suggested that cognitive performance and memory processes are coupled with remodeling of pyramidal dendritic spine synapses in prefrontal cortex (PFC), and that reduced spine density and number of spine synapses in the medial PFC of PCP-treated rats may potentially underlie, at least partially, the cognitive dysfunction previously observed in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 62 publications
(77 reference statements)
4
26
0
Order By: Relevance
“…LY379268 was similarly effective as olanzapine in restoring NMDA-R and GABAA-R binding levels in the two-hit model. Research by Elsworth and colleagues has shown that chronic PCP-induced dendritic spine loss can be restored by a single olanzapine injection within 90 min of treatment (Elsworth et al, 2011), a mechanism possibly contributing to the recovery of NMDA-R and GABAA-R binding levels. Olanzapine, however, did not restore the positive correlation between NMDA-R and GABAA-R binding levels, while LY379268 did.…”
Section: 3mentioning
confidence: 99%
“…LY379268 was similarly effective as olanzapine in restoring NMDA-R and GABAA-R binding levels in the two-hit model. Research by Elsworth and colleagues has shown that chronic PCP-induced dendritic spine loss can be restored by a single olanzapine injection within 90 min of treatment (Elsworth et al, 2011), a mechanism possibly contributing to the recovery of NMDA-R and GABAA-R binding levels. Olanzapine, however, did not restore the positive correlation between NMDA-R and GABAA-R binding levels, while LY379268 did.…”
Section: 3mentioning
confidence: 99%
“…A single injection of PCP (10 mg/kg) to rats on P7 caused selective reduction in Pv-containing, not calretinin-or calbindin-containing, interneurons in cortical areas in early adulthood (P56) (Wang et al, 2008a). A persistent decrease in the number of PFC spine synapses, in parallel to the cognitive deficits, was evident with twice daily injection of 5 mg/kg of PCP for 7 days (Elsworth et al, 2011b). These PCP effects on gene regulation are important examples of the widespread actions of PCP on neural tissue, which appear to produce long-term changes in the nervous system.…”
Section: F N-methyl-d-aspartate Receptor Antagonistsmentioning
confidence: 99%
“…As briefly mentioned above, while we did not observe hippocampal levels of myelin related proteins to be significantly altered in PCP treated rats compared to controls, we did notice that hippocampal levels of these proteins were not significantly different from those observed in the prefrontal cortex of PCP treated rats, whereas in control rats these levels were significantly different at PN12 (Figure 3). We hypothesize that the lack of a statistically significant difference in the hippocampus compared to the prefrontal cortex levels of myelin related proteins in PCP treated rats, may be playing a role in some of the PCP induced cognitive deficits that are observed in rodent models of schizophrenia, long-term abusers of PCP [38], and in schizophrenia patients [45]. In support of this, injections of potent demyelination agents into the ventral hippocampus of 10 day old rat pups has been shown to induce a variety of schizophrenia related endophenotypes, including deficits in prepulse inhibition, hyper locomotion and inducing anxiety related behaviors, suggesting that demyelination plays an important role in the development and severity of schizophrenia [60].…”
Section: Hippocampal Levels Of Wave1 But Not Nwasp or Myelin Related mentioning
confidence: 99%
“…Similarly, PCP administration in rats has been shown to significantly reduce the number of dendritic spine synapses in the prefrontal cortex, for up to 4 weeks following the cessation of PCP treatment [37,38], and induce significant cognitive impairment in both monkeys [39] and rats [40][41][42][43]. NWASP and WAVE1 are important regulatory proteins involved in maintaining the actin cytoskeleton [22] and are critical for the development of dendritic spines and synapses [24,25].We have shown NWASP and WAVE1 protein expression to be significantly reduced in the prefrontal cortex of juvenile PCP treated rats compared to controls.…”
Section: Nmda Receptor Antagonism By Pcp Acutely Reduces Expression Omentioning
confidence: 99%